Pengaruh Keputusan Bauran Promosi Terhadap Pengambilan Keputusan Pembelian Nomor Perdana Telkom Flexi di Kota Banjarmasin - Sri Imelda; Marijati Sangen (Universitas Lambung Mangkurat, 2013)
This study aims to determine the influence of the promotion mix (advertising, personal selling, sales promotion, public relations, and direct marketing and on-line) partial and simultaneous decision to purchase prime numbers TELKOMFlexi in Banjarmasin city. This research was conducted using a survey method, which is carried out on 219 respondents spread across five districts in the city of Banjarmasin. This is a descriptive study and verification. Data were collected by distributing questionnaires, interviews and document searches, while the method of data analysis is a data analysis using Structur Equetion Modelling (SEM). The results showed that the promotional mix consisting of: advertising, sales promotion, personal selling, do not have a significant influence on the purchase decision process TelkomFlexi Prime Numbers in Banjarmasin city, while the variables that are significant public relations and direct marketing to the buying decision process Prime Numbers TelkomFlexi in the city of Banjarmasin.